Ordinal Measures in Multiple Indicator Models: A Simulation Study of Categorization Error - Johnson, David Richard; Creech, James C. (American Sociological Review, 1983)
David Richard Johnson, James C. Creech, Ordinal Measures in Multiple Indicator Models: A Simulation Study of Categorization Error, American Sociological Review, Vol. 48, No. 3 (Jun., 1983), pp. 398-407